2017
DOI: 10.1038/s41598-017-02379-8
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic nematode Meloidogyne incognita interactions with different Capsicum annum cultivars reveal the chemical constituents modulating root herbivory

Abstract: Plant volatile signatures are often used as cues by herbivores to locate their preferred hosts. Here, we report on the volatile organic compounds used by the subterranean root-knot nematode (RKN) Meloidogyne incognita for host location. We compared responses of infective second stage juveniles (J2s) to root volatiles of three cultivars and one accession of the solanaceous plant, Capsicum annum against moist sand in dual choice assays. J2s were more attracted to the three cultivars than to the accession, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(148 citation statements)
references
References 53 publications
8
139
0
1
Order By: Relevance
“…Although we have demonstrated that octadecanoic acid is an inhibitor of PPN attraction in previous work (Cox et al, 2019a), our data suggest that it is not a biologically relevant inhibitor following ERF-E2 knockdown, despite being significantly elevated, along with 2,3dimethylpropyl octadecanoate (Figure 3). This suggests that other compositional changes have a greater influence on PPN behaviour in this context; similar observations have been documented previously (Kihika et al, 2017). The GC-MS data also demonstrate a substantial developmental influence on exudate composition, with control exudates exhibiting clear differences between week 3 and week 4-post inoculation.…”
Section: Moneymakersupporting
confidence: 86%
“…Although we have demonstrated that octadecanoic acid is an inhibitor of PPN attraction in previous work (Cox et al, 2019a), our data suggest that it is not a biologically relevant inhibitor following ERF-E2 knockdown, despite being significantly elevated, along with 2,3dimethylpropyl octadecanoate (Figure 3). This suggests that other compositional changes have a greater influence on PPN behaviour in this context; similar observations have been documented previously (Kihika et al, 2017). The GC-MS data also demonstrate a substantial developmental influence on exudate composition, with control exudates exhibiting clear differences between week 3 and week 4-post inoculation.…”
Section: Moneymakersupporting
confidence: 86%
“…An alternative explanation might be that herbivory changes plant attractiveness by influencing, for instance, root exudation or root volatile emission patterns. Nematodes exploit systemically induced root volatiles for host location (Ali, Alborn, & Stelinski, 2011;Kihika, Murungi, & Coyne, 2017;Massalha, Korenblum, Tholl, & Aharoni, 2017). Further studies might aim at investigating the relative contribution of these effects to herbivory induced facilitation of nematode infestation.…”
Section: Discussionmentioning
confidence: 99%
“…At the site of infection they induce galls or root‐knots which affect the nutritional status of the plant causing yield losses and consequently a reduction in product quality . Volatiles produced by roots of Capsicum annuum , such as α‐pinene and limonene, elicited positive chemotaxis in Meloidogyne incognita , with methyl salicylate showing the highest effect in terms of attraction . Recently Čepulytė et al .…”
Section: Roles Played By Plant Signaling Molecules In the Soil Ecosystemmentioning
confidence: 99%
“…103 Volatiles produced by roots of Capsicum annuum, such as -pinene and limonene, elicited positive chemotaxis in Meloidogyne incognita, with methyl salicylate showing the highest effect in terms of attraction. 104 RecentlyČepulytė et al 105 found in tomato and Medicago root exudates from seedling root tips, powerful -non-volatile -attractant(s) for three root-knot nematode species, but could not identify them. It is unclear whether root-knot nematodes use host-specific cues or rather a non-specific blend of volatile and non-volatile compounds.…”
Section: Plant-nematode Interactionmentioning
confidence: 99%